2017
DOI: 10.1680/jadcr.16.00020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and mechanism study of temperature-resistant fluid loss reducer for oil well cement

Abstract: A novel temperature-resistant fluid loss reducer FL is obtained by free radical copolymerisation. Thermal gravimetric analysis demonstrates that the fluid loss reducer FL has a strong temperature-resistance capability and its degradation temperature is higher than 440°C. An experiment investigating the effect of FL on the comprehensive performance of oil well cement slurry shows that filter loss can be controlled within 50 ml when the dosage of FL is 1·0% of the total mass of cement and quartz powder under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…And after testing under different water quality conditions, it was found that its water loss effect is not affected by the water quality. Yan et al [116] obtained a novel temperatureresistant copolymers by the free radical copolymerization of AA, AM, SSS, and acrylate poly (ethylene glycol) (APEG) with hydrophilic long chain. The obtained copolymers as filtrate reducer exhibited high ability to control fluid loss.…”
Section: Polymeric Filtrate Reducers From Am-based Copolymersmentioning
confidence: 99%
“…And after testing under different water quality conditions, it was found that its water loss effect is not affected by the water quality. Yan et al [116] obtained a novel temperatureresistant copolymers by the free radical copolymerization of AA, AM, SSS, and acrylate poly (ethylene glycol) (APEG) with hydrophilic long chain. The obtained copolymers as filtrate reducer exhibited high ability to control fluid loss.…”
Section: Polymeric Filtrate Reducers From Am-based Copolymersmentioning
confidence: 99%
“…The Tarim Oilfield reservoirs generally have a large burial depth and well-developed salt formations, which pose significant challenges for water-based drilling fluids in terms of both prolonged hightemperature exposure and high salinity environments [1][2][3][4][5]. To enhance the temperature and salt resistance properties of filtration control agents, two main traditional approaches have been employed [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%